Pulsed light as an emerging technology to cause disruption for food and adjacent industries – Quo vadis?. (June 2019) - Rowan, Neil J.
Abstract: Background: – Despite verbose amount of publications and having gained approval by Food and Drug Administration (FDA) since 1996 for food-surface disinfection applications, pulsed light (PL) still has not been used on a large scale by industry. Fresh produce remains a leading cause of foodborne illness outbreaks where there is a pressing need for an effective post-harvest decontamination intervention such as PL that can replace or supplement post-harvest washing. Scope and approach: This review describes current status of PL for non-thermal food-surface treatments. It addresses rationale and efficacy of methods used to assess PL disinfection performance along with addressing inter-related factors that are limiting PL development for these opportunities. Key findings and conclusions: PL is a promising non-thermal technology for food-surface disinfection. Lack of international harmonisation and consensus on what constitutes priority experimental methods and exposure conditions is hampering commercial development of PL. Previously, many studies have reported on PL-food treatments using a cumulative energy dose or range of UV doses above the FDA recommended 12 J cm −2 . Consensus on the choice and relevance of indirect cell and molecular methods to assess injury in PL-treated microorganisms has yet to be reached. This review provides recommendations in reporting experimental data and key parameters governing treatment that enables reporting of sufficient details to extent that other researchers would be able to repeat, compare and evaluate data between studies. Converging developments in adjacent industry sectors that may inform development of PL as a promising future food disruptive technology are described. Highlights: Pulsed light (PL) has not been taken up on a large scale by the food industry despite approved by FDA in 1996. Many published studies use cumulative energy dose(s) above the FDA recommended 12 J cm −2 . PL is a promising technology for decontamination of fresh produce post-harvest. Guidelines are provided for harmonising PL experimental data and exposure conditions. PL has potential to cause first and second order technology disruption across many applications.